Presidente, Martínez de Velasco : abre el libr. Antonio Royo Villanova ; la cierra, José Martínez de Velasco / Teófilo Ortega - Royo Villanova, AntonioMartínez de Velasco, José; Ortega, Teófilo (1905-1965?)
Retrato de José Martínez de Velasco